Islam and the West post 9/11 - Geaves, Ron (Ashgate Pub., 2004)
This book offers a chance for greater understanding of the political and religious groups in Islam that have contributed to events pre and post September 11th, and clearer insights into Muslim/Christian relations today. Many books have focused on the events of September 11th but have been primarily journalistic. This book draws together both Muslim and non-Muslim scholars who have been studying Christian/Muslim relations for many years. They assess the impact of 9/11 on Islamophobia and antipathy towards Muslims. Providing insights into various multi-cultural communities whose relations with Islam have been affected, the authors look particularly at regions where there are large minority Muslim communities (US and UK) and large minority non-Muslim communities (Indonesia and Nigeria)." "Assessing a number of issues impacting upon the teaching of Islam, this book allows readers to assess the consequences of the event and develop a more critical understanding of its implications.